Increasing Rural Economic Empowerment Through Inclusive Finance: A Case Study of Dolokgede Village, East Java - Astuti, Nelly; Akbar, Jufri Sani; Makrus, Mohammad (International Journal of Business and Applied Economics, 2024)
Financial inclusion is one of the main pillars in efforts to eradicate poverty and improve community welfare.  This research aims to explore how financial inclusion programs can be implemented more effectively in rural communities by considering local needs and characteristics. This research used mixed methods on village communities in Dolokgede, East Java. The population in this study was the entire community of Dolokgede village. Samples were taken using purposive sampling as many as 312 people. Primary data was collected through surveys. The research results show that the financial inclusion program has had a significant impact on improving the economic welfare of the community in Dolokgede Village by providing better access to capital and financial services.